CLASSIFICATION OF SUB-LEVELS IN TURKEY WITH GUSTAFSON-KESSEL METHOD - Özge Gündoğdu; Necati Erilli (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The European Unionpaved the way for countries to be divided into sub-units and in a sense pavedthe way for the further elaboration of statistical calculations. Level-1 orLevel-2 classifications, which are created not only by the cities but also withneighboring cities, are of great importance in the development calculations ofcountries. Fuzzy Clustering approach comes out as a suitable method if theclusters are not separated from each other prominently or if some of themembers are indecisive about being a member of the cluster. Fuzzy clusters arefunctions that determine each unit between 0 and 1 defined as the membership ofthe unit. Units which are very similar take part in the same cluster accordingto high membership degree. The purpose here is to determine homogenous citygroups that have the same characteristics in terms of these indicators. In thisstudy, one of the well known fuzzy clustering methods Gustafson-Kessel is usedfor classification SCTU Level-2 regions through development indicators. Theresults obtained from the Level-2 classifications were also used to rank theregions according to their importance. Thus, priority regions can be determinedin investments.